If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8b+4=10b-4
We move all terms to the left:
8b+4-(10b-4)=0
We get rid of parentheses
8b-10b+4+4=0
We add all the numbers together, and all the variables
-2b+8=0
We move all terms containing b to the left, all other terms to the right
-2b=-8
b=-8/-2
b=+4
| 16x16x=13x | | 13x–22=9x–6 | | 1.5n-10=20 | | -8(q+34)=8 | | 2(x+1)=(4-2x) | | s-33=-8 | | y=0.12(1005)+0 | | 4×(z÷7)-8=-1 | | 10=-14t-2 | | 238-v=78 | | 10(3x+12)=170 | | 3w+71=7w-25 | | 8/2=x-11/3 | | 1=y/4−2 | | 9+8k=49 | | 56-1x=11x+106 | | 2xx23=27 | | 8x1=8x+1 | | 178=125-v | | 38x-25x+18=20 | | –3u=6 | | 8a-8a=0 | | c.40=5c | | 5(c-15)=-10 | | 35=y–6 | | 45=3(r-59) | | 4-9x=41 | | 29=-y+290 | | (3x+67)=(4x+50) | | y+27=12 | | 6a+5a–1=21 | | 45=7/6u |